Interposition arthroplasty with bovine collagenous membrane for hallux rigidus: A long-term results retrospective study. Issue 8 (December 2022) - Colò, Gabriele; Fusini, Federico; Alessio-Mazzola, Mattia; Samaila, Elena Manuela; Formica, Matteo; Magnan, Bruno
Abstract: Background: Hallux rigidus (HR) is a degenerative arthritis of the first metatarsophalangeal joint (MTP1) with progressive loss of range of movement (ROM). Interposition arthroplasty (IA) is a technique widely used for the treatment of HR;however, few studies reported long-term clinical results. This study aims to report the clinical results of IA using a bovine pericardium collagen matrix for HR with a minimum 10-years follow-up. Methods: Thirty patients (31 feet) who underwent IA using a bovine pericardium collagen matrix from 2001 to 2009 were retrospectively evaluated with a mean follow up of 154.1 ± 28.6 (range 124–218) months. All HR ranged from grade II to grade III, according to Regnauld classification. All patients were clinically assessed with the American Orthopedic Foot and Ankle Society Hallux Metatarsophalangeal- Interphalangeal Scale, a pain Visual Analog Scale, and the Foot and Ankle Disability Index. Scores before and after treatment, respectively achieved from clinical records and clinical evaluation at final follow-up were compared. Results: At final follow-up, an improvement of all the considered scores (p < 0.01) was recorded. The overall rate of unsatisfying results was 16.1 %. Two (6.4 %) patients complained discomfort due to first ray shortening and 3 (9.7 %) cases of persistent metatarsal pain. There was one (3.2 %) case of Complex Regional Pain Syndrome (CPRS). No revision surgeries, infection, or other adverse events were reported.Conclusion: Interposition arthroplasty using bovine collagenous membrane is a reliable solution for high-grade HR with durable results over 10 years in more than 80 % of patients.